ASSESSMENT OF THE NUTRITIONAL QUALITY OF BAMBARA GROUNDNUT CONDIMENT (BGNC) AND CONSUMER ACCEPTABILITY OF BGNC IN OKRO SOUP - OLANIPEKUN, O.T.; AKINLOYE, O.A.; UGBAJA, R.N.; AFOLABI, T.A.; ASHAYE, O.A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Food insecurity is a major problem in African countries. Increasing food diversity will improve the availability of food, thereby reducing food insecurity. A dadawa-like product (Bambara groundnut condiment-BGNC) was made from Bambara groundnut. Nutritional composition, protein quality and consumer acceptability of the product were assessed using standard methods. Consumer acceptance of BGNC compared favourably with dadawa (DDW), a popular fermented condiment (made from Parkia biglobosa) in South-West, Nigeria. The protein content of BGNC (21.69 %) compared to that of dadawa (21.41 %). Magnesium, phosphorus and potassium concentrations were higher in BGNC than in DDW (69.04 vs 28.23, 189.13 vs 78.22, 82.26 vs 19.43) mg/100g for BGNC vs DDW respectively. The protein quality of Bambara groundnut condiment-based feed compared fairly well with that of other protein sources like fish and casein. The possibility of making condiment from Bambara groundnut was ascertained in this study. Bambara groundnut condiment was well accepted by consumers. The acceptance compared favourably well with dadawa; as there was no significant difference (p>0.05) in appearance, taste and overall acceptability of BGNC and DDW when used to garnish okro soup. Consumers of the Bambara groundnut condiment will benefit from its high nutritional value.